2004
DOI: 10.1002/bdm.463
|View full text |Cite
|
Sign up to set email alerts
|

Decision framing: moderating effects of individual differences and cognitive processing

Abstract: Two studies examined the effect of an individual difference variable, need for cognition (NC), and processing of the options on the occurrence of risky choice framing effects. In Study 1 (N ¼ 206), frame interacted with NC and math skill such that no framing effect was observed among those high in both NC and math skill. No effect was found for the processing manipulation of requesting a reason for one's choices. Study 2 (N ¼ 257) enhanced the processing of the problems by asking participants to write out the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 42 publications
4
93
2
3
Order By: Relevance
“…Fear of failure has been shown to influence opportunity related cognitions and decision making (Mitchell and Shepherd 2010;Wood and Rowe 2011), and social psychology research has also shown that individual differences can mitigate framing effects (Simon, Fagley, and Hallerman 2004). The implication for our model is that fear of failure may impact the risk tolerance, desirability, and feasibility cognitions associated with the loss framing engendered by layoff or long-term unemployment.…”
Section: Moderating Role Of Fear Of Failurementioning
confidence: 82%
“…Fear of failure has been shown to influence opportunity related cognitions and decision making (Mitchell and Shepherd 2010;Wood and Rowe 2011), and social psychology research has also shown that individual differences can mitigate framing effects (Simon, Fagley, and Hallerman 2004). The implication for our model is that fear of failure may impact the risk tolerance, desirability, and feasibility cognitions associated with the loss framing engendered by layoff or long-term unemployment.…”
Section: Moderating Role Of Fear Of Failurementioning
confidence: 82%
“…The qualities of the mind suspected as playing a role in the decision making are either the natural need to make reflective and difficult choices or mathematical literacy. Indeed in the study by Simon, Fagley and Halleran (2004) people with a high level of the need for cognition and high self-evaluation of their mathematical skills displayed no framing effect in the Asian disease scenario, while in the participants with a low need for cognition, the framing effect was obtained regardless of their mathematical skills. Frederick (2005) assumed that both logical and mathematical skills, as well as the motivation to suppress intuitive answers would influence decision making when the decision problems call for the rules of normative reasoning.…”
Section: Asian Disease As a Classical Scenario For Framing Studiesmentioning
confidence: 79%
“…For example, there has been a good deal of recent interest in how the style of processing (McElroy & Seta, 2003;Igou & Bless, 2007;Stanovich, 2008), memory retrieval (Reyna & Brainerd, 1991), emotional-rational inconsistencies (Wang, 2006) and individual differences (Chatterjee, Heath, Milberg & France, 2000;Levin, Gaeth, Scheriber & Lauriola, 2002;Xie & Wang, 2003;Simon, Fagley & Halleran, 2004;Wang, 2004;McElroy, Seta &Waring, 2007;Dickinson & Drummond, 2008) play out in the framing process and decision choice. Further, this may provide insight on recent findings that show incompatibility between trust and choice in decision-making (Keren, 2007).…”
Section: Discussionmentioning
confidence: 99%